Eosinophil–Epithelial Cell Interactions Stimulate the Production of MUC5AC Mucin and Profibrotic Cytokines Involved in Airway Tissue Remodeling. Issue 2 (March 2014) - Shimizu, Shino; Kouzaki, Hideaki; Ogawa, Takao; Takezawa, Kumiko; Tojima, Ichiro; Shimizu, Takeshi
Background: Predominant eosinophil infiltration and tissue remodeling are common characteristics of chronic airway inflammation such as nasal polyposis and bronchial asthma. This study was designed to elucidate the role of eosinophils in tissue remodeling of chronic airway inflammation; eosinophil–epithelial interactions were examined by the coculture of airway epithelial cell line NCI-H292 with the eosinophilic cell line EoL-1 or with human blood eosinophils. Methods: The coculture-induced production of MUC5AC mucin, platelet-derived growth factor AB (PDGF-AB), vascular endothelial growth factor (VEGF), transforming growth factor (TGF) beta1, and interleukin-8 (IL-8) were evaluated by enzyme-linked immunosorbent assay and reverse transcription–polymerase chain reaction. Results: Eosinophil–epithelial interactions significantly stimulated the secretion of MUC5AC, PDGF-AB, VEGF, TGF-beta1, and IL-8 in culture supernatants. The epidermal growth factor receptor tyrosine kinase inhibitor AG1478 inhibited the coculture-induced secretion of MUC5AC, PDGF-AB, VEGF, and IL-8. Neutralizing antibodies directed against TGF-alpha or amphiregulin and pan-metalloproteinase inhibitor GM6001 inhibited the coculture-induced secretion of MUC5AC and amphiregulin from the cocultured NCI-H292 cells. Coculture of NCI-H292 cells with peripheral blood eosinophils also significantly stimulated MUC5AC production. Conclusion: The results of this study indicate that eosinophil–epithelial cell interactions are important in the pathogenesis of tissue remodeling of eosinophil-predominant airway inflammation such as occurs in nasal polyposis and bronchial asthma.